Photovoltaic Thermal District Heating: A review of the current status, opportunities and prospects. (25th November 2022) - Kang, A.; Korolija, I.; Rovas, D.
Abstract: This work presents a first-of-its-kind review specifically on photovoltaic thermal district heating (PVT DH), compiling a wide range of sources information to view and analyse its current status. From this, interesting conclusions have been extrapolated that would otherwise be unreachable without this holistic view. Potential opportunities have also been identified in the use of PVT panels in conjunction with other heating technologies, such as heat pumps, for its application in DH. Sources used included academic literature, government reviews, environmental agencies, manufacturers, energy and finance news, industrial and a German installation report. The review starts with a discussion on the need for decarbonising heating in urban areas and introduces how PVT DH could be a potential solution. This is followed by a discussion on PVT technology in terms of efficiency, status and market. Due to the diurnal/seasonal nature of PVT, an overview of potential storage technologies was then provided. The review identified that it is evident there are various 'off the shelf' storage technologies ready to be implemented in PVT DH systems. Following this, a discussion on PVT DH installations and studies investigates the advantages and disadvantages of this system. It is concluded that there is a need for future research to focus on the control strategies for PVT DH, taking into account the requirement to keep the PVT temperature low to optimise the electrical efficiency, and the integration of thermal storage and/or heat pumps. Finally, the review summarises how this investigation has led to the discovery of several external drivers which could put PVT DH ahead as a potential option when choosing clean heating strategies in the future. These include; progression towards 4 th generation district heating, solar technology and storage technological advancement and cost reduction, mutual system performance improvement with heat pumps, and green legislation/policies. If knowledge and working experience of PVT DH systems can be expanded, particularly in control strategies, the system performance can be enhanced making it an attractive option for 4 th generation district heating systems. Highlights: Drivers identified which could make photovoltaic thermal district heating an attractive option. Research gap identified in control strategies for photovoltaic thermal district heating. Mutually beneficial energy synergies between photovoltaic thermal district heating system counterparts. Work is required to expand the photovoltaic thermal district heating market.